A viable insolvency procedure for sovereigns (VIPS) in the euro area - Clemens Fuest; Friedrich Heinemann; Christoph Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
A mechanism to restructure the debt of an insolvent euro country is a missing element in the emerging institutional architecture of the euro area. The introduction of an insolvency procedure for sovereigns faces a dilemma: In the foreseeable future, its introduction would risk pushing Europe back into acute crisis. But the indefinite postponement of reform would impair the credibility of a future regime change. Against this background, this paper reviews arguments and existing blueprints for sovereign insolvency procedures in the euro area and develops a 'Viable Insolvency Procedure for Sovereigns' (VIPS). VIPS avoids any sudden measures which could destabilize the present fragile situation but carefully designs an irreversible transition towards the new regime. The VIPS proposal comprises two pillars: An insolvency procedure for the long run and a credible bridge towards that system.
urn:nbn:de:bsz:180-madoc-369906
Keywords: F34; H12; H63; 330; euro area debt crisis; sovereign insolvency procedure